Strategies to Enhance Student Discipline through an Islamic Education Approach - Taufik Abdurrahman; Feby Irwansyah; Siti Roudhotul Jannah (Edutechnium Journal of Educational Technology, 2026)
This study aims to describe effective strategies for enhancing student discipline through an Islamic education approach. Student discipline constitutes a fundamental pillar in character formation and the creation of a conducive learning environment. Within the perspective of Islamic education, discipline encompasses not merely compliance with external regulations but also the cultivation of spiritual awareness, moral integrity, and consistent commitment (iltizam) to divine commands. This research employs a qualitative method with a library research approach, analyzing data from academic books, scientific journal articles, dissertations, and previous relevant studies published between 2020 and 2025. The findings reveal that six primary strategies are effective in shaping student discipline: (1) role modeling (uswah hasanah) by teachers and parents; (2) habituation of worship practices (ibadah), including congregational prayers and Qur‘anic recitation; (3) integration of moral values (akhlak) across the curriculum; (4) implementation of educative reward and punishment systems based on targhib and tarhib principles; (5) strengthening of Islamic school culture through consistent religious routines; and (6) active involvement of parents and the broader community. The results indicate that an integrated, holistic approach addressing cognitive, affective, and psychomotor domains yields the most sustainable improvements in student discipline. This article contributes theoretical and practical insights for educators, educational administrators, and policymakers in implementing Islamic value-based character education within formal schooling contexts.